Mechanochemical Synthesis of Potassium–Ion Conductor K3SbS4 - Takehiro NAKAO; Chihiro OKUSHIMA; Takuya KIMURA; Akira NASU; Kota MOTOHASHI; Atsushi SAKUDA; Akitoshi HAYASHI (Electrochemistry)
Antimony-based sulfide solid electrolytes exhibit high conductivity for alkaline cations. In this study, we synthesized K3SbS4 potassium-ion conductors using the mechanochemical method for the nominal compositions with x mol% excess K2S (x = 0, 5, 10, and 15) to compensate for the chemical impurities in the K2S reagent. The mechanochemically prepared samples showed X-ray diffraction patterns similar to β-K3SbS4 in all the compositions. Raman bands attributed to the SbS43− unit were observed in all the samples. The ionic conductivities at 25 °C showed a positive correlation with increasing x, reaching a maximum ionic conductivity of 3.6 × 10−6 S cm−1 at 10 mol% excess K2S. Subsequent heat-treatment further enhanced the ionic conductivity, achieving 1.2 × 10−5 S cm−1 at 25 °C. This improvement is attributed to the nominal composition being close to that of K3SbS4 by adjusting the excess amount of K2S and the increased crystallinity of β-K3SbS4.